ANALYSING CHALLENGES OF DEVELOPING ECOTOURISM VILLAGE IN SLEMAN, YOGYAKARTA, INDESIONA: A COMMUNITY DEVELOPMENT APPROACH - Prayudi, .; Susilo, Edy; Herastuti, Heti (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this research is to analyse challenges faced in developing ecotourism village in Indonesia. Issue of sustainability has become a debate among scholars as to how the development of ecotourism village will benefit society or villagers and at the same time preserve environment and traditional values. Further, the research also identifies the capacity of human resources in developing ecotourism village. It’s argued that if relevant factors in initiating the development of ecotourism village can be identified, suitable programs can be developed and implemented from small to large scale, enhance the life of villagers, and preserve natural as well as cultural environments. This study used qualitative research method. This method systematically describes the facts or characteristics of a particular population or a particular field factually and accurately. Findings of research indicate some challenges if ecotourism village in Sleman, Yogyakarta, Indonesia is to develop. The first is to change the mindset and to build awareness of villagers. It is because the villagers will be the main actors that will run the ecotourism village. Second is to identify village potentials to be develop and becomes the uniqueness of the village. Third is how local government regulate and protect the development of ecotourism village. Fourth is to involve other tourism actors in the process. Based on the findings, outcomes of research are programs that need to carry out and at the same time involve villagers in developing ecotourism village. Future research is needed as to how to involve other stakeholders in contributing to the development of ecotourism village.